Efektivitas Terapi Film dalam Meningkatkan Empati - Balqis Arwa Aziizah; Muhammad Fikri Izzuddin; Raden Aurora Sativa Hawa Gantara; Sri Mulyeni (Pusat Riset dan Inovasi Nasional, 2026)
Empathy is a fundamental skill that plays a role in supporting healthy social interactions, psychological well-being, and the creation of a positive academic climate in higher education environments. In the context of higher education, empathy contributes to improving the quality of interpersonal relationships, social awareness, and the ability to understand other people's perspectives. One approach that can be used to develop empathy is film therapy, which is the use of audiovisual media as a means of cognitive and affective reflection. This study aims to examine the effect of film therapy on students' empathy levels using the short film Indifferent as the intervention medium. This study uses a quantitative approach with an experimental method and a pretest-posttest design. The research subjects consisted of 27 active students who participated in the entire research process. Empathy was measured twice, before and after the film screening, using a five-point Likert scale empathy questionnaire. The data were analyzed using a paired sample t-test to determine the difference in empathy levels before and after the intervention. The results of the analysis showed an increase in empathy scores among students after participating in film therapy, although the increase did not reach statistical significance. These findings indicate that film therapy has a moderate effect in increasing empathic awareness through emotional involvement and self-reflection processes. In conclusion, film therapy has the potential to be used as an affective learning medium and alternative intervention in higher education and guidance and counseling services, although further research with a larger number of subjects and longer intervention duration is needed.